Molecular Basis of Prodrug Activation by Human Valacyclovirase, an α-Amino Acid Ester Hydrolase - Longsheng Lai; Zhaohui Xu; Jiahai Zhou; Kyung-Dall Lee; Gordon L. Amidon (2008)
Chemical modification to improve biopharmaceutical properties, especially oral absorption and bioavailability, is a common strategy employed by pharmaceutical chemists. The approach often employs a simple structural modification and utilizes ubiquitous endogenous esterases as activation enzymes, although such enzymes are often unidentified. This report describes the crystal structure and specificity of a novel activating enzyme for valacyclovir and valganciclovir. Our structural insights show that human valacyclovirase has a unique binding mode and specificity for amino acid esters. Biochemical data demonstrate that the enzyme hydrolyzes esters of alpha-amino acids exclusively and displays a broad specificity spectrum for the aminoacyl moiety similar to tricorn-interacting aminopeptidase F1. Crystal structures of the enzyme, two mechanistic mutants, and a complex with a product analogue, when combined with biochemical analysis, reveal the key determinants for substrate recognition; that is, a flexible and mostly hydrophobic acyl pocket, a localized negative electrostatic potential, a large open leaving group-accommodating groove, and a pivotal acidic residue, Asp-123, after the nucleophile Ser-122. This is the first time that a residue immediately after the nucleophile has been found to have its side chain directed into the substrate binding pocket and play an essential role in substrate discrimination in serine hydrolases. These results as well as a phylogenetic analysis establish that the enzyme functions as a specific alpha-amino acid ester hydrolase. Valacyclovirase is a valuable target for amino acid ester prodrug-based oral drug delivery enhancement strategies.